2005
DOI: 10.1136/bmj.38470.670903.e0
|View full text |Cite
|
Sign up to set email alerts
|

Early life risk factors for obesity in childhood: cohort study

Abstract: Eight factors in early life are associated with an increased risk of obesity in childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

80
1,168
12
51

Year Published

2006
2006
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,409 publications
(1,311 citation statements)
references
References 23 publications
80
1,168
12
51
Order By: Relevance
“…Prenatal smoking and child overweight Our literature review yielded 14 studies eligible for inclusion in the meta-analysis of smoking and overweight risk [14][15][16][17][18][19][20][21][22][23][24][25][26][27] ( Table 1). These studies included 84 563 children, and represent pregnancies that occurred from 1958 to 2002 in low and non-low income populations in Australia, North America, and Europe.…”
Section: Resultsmentioning
confidence: 99%
“…Prenatal smoking and child overweight Our literature review yielded 14 studies eligible for inclusion in the meta-analysis of smoking and overweight risk [14][15][16][17][18][19][20][21][22][23][24][25][26][27] ( Table 1). These studies included 84 563 children, and represent pregnancies that occurred from 1958 to 2002 in low and non-low income populations in Australia, North America, and Europe.…”
Section: Resultsmentioning
confidence: 99%
“…18,42 These techniques demonstrate higher adiposity in children up to the age of 7 years and also in adults between 18 and 24 years who were born to mothers with raised BMI, and/or exposed to gestational diabetes in utero. [45][46][47][48] The association between raised maternal BMI and LGA birthweight or raised neonatal adiposity implies a direct effect on the developing fetus of an adverse uterine environment during pregnancy. It is difficult however to determine whether in the long term, raised BMI and adiposity in the offspring of obese mothers occur directly due to adverse uteroplacental priming of the fetus during the obese pregnancy (versus inherited genetic influences), or as a result of the indirect environmental influence of an "over-fed" home.…”
Section: Childhood Obesitymentioning
confidence: 99%
“…In these cross-sectional studies, parental obesity, low socio-economic status (SES), high weight gain during infancy and television (TV) viewing were found as main determinants of prevalence. Contrary to cross-sectional data, there are only very few longitudinal studies investigating the development of overweight (14,(18)(19)(20)(21) . In these studies parental overweight was found as the main determinant.…”
mentioning
confidence: 99%